Impact of fertigation and drip system layout on performance of chilli (capsicum annum) - NADIYA NESTHAD; Dr. Kurien E. K (Guide) (Tavanur 2012 DEPARTMENT OF LAND &WATER RESOURCES AND CONSERVATION ENGINEERING)
The statistical design was fuctorial randomized block design consisted of 21 plots with seven treatments and three replications. the growth and the yield parameters were compared statistically.
Impact of fertigation and drip system layout on performance of chilli (capsicum annum)